Perancangan sistem informasi akuntansi penerimaan dan pengeluaran kas di Star Glam Bandung - Novyanti, Dian Qolby; Nursyabani, Rizki Amalia; Karyadi, Karyadi; Abdussalaam, Falaah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The objective of this research is designing accounting information system of cash receipts and disbursements cash in Star Glam Bandung. This research used qualitative method to collect the data, all of the data were carried by observation and literature review of theoretical study concerning the topic. Based on the research, there was a problem in recording cash receipts and disbursements cash process. It was still manually and less effective, so that take more time in the process. The problem basically can be solve by develop the information sistem in software by using Waterfall model that has five stages and also Flowmap model and Data Flow that was implemented by Microsoft Visual Studio 2010 and Microsoft Access as database. Based on the results of research conducted by the author, it can be concluded that the existence of an information system for cash receipts and disbursements at Star Glam Bandung makes the process of recording and inputting data easier and minimizes errors. With the information system is also able to generate reports of cash receipts and disbursements more quickly, precisely and accurately.